Serum nitric oxide and malondialdehyde in a hypertensive population in Sokoto, Nigeria - M., Yale B.; H., Yeldu M. (International Journal of Research in Medical Sciences, 2018)
Background: Hypertension is recognized as most common cardiovascular disorder and a leading cause of morbidity and mortality worldwide. Endothelial dysfunction, which is associated with impaired nitric oxide is an important risk factor for both hypertension and cardiovascular diseases. There is abnormal lipid peroxidation which suggested that oxidative stress is important in the pathogenesis of hypertension. This study assessed serum levels of nitric oxide and malondialdehyde in hypertensive population in Sokoto-Nigeria. Methods: A total of 474 subjects who are within the age range of 25 to 76 years, including 316 hypertensive patients and 158 age- and sex- matched normotensive subjects were included in this study. Clinical and anthropometric parameters, nitric oxide and malondialdehyde were measured using standard techniques. Results: The result indicated that, mean systolic blood pressure (SBP) was significantly (p˂0.001) higher in hypertensive patients (166.00±1.39mmHg) than controls (124.97±0.95 mmHg) similarly the mean BMI was significantly (p˂0.001) higher in hypertensive patients (27.13±0.31 Kg/m2) than controls (23.54±0.12Kg/m2). Mean serum malondialdehyde (MDA) was significantly (p˂0.001) higher in hypertensive patients (3.62±0.07µmol/L) as compared to controls (1.97±0.03µmol/L), while serum nitric oxide (NO) was significantly (p=0.009) lower among hypertensive patients (7.12±0.14µmol/L) than controls (15.26±0.15µmol/L). Conclusions: Hypertension is a complex disorder that is strongly associated with other risk factors for cardiovascular disease. The aetiology of the association between impaired NO bioactivity, increase MDA and hypertension has not been fully elucidated. Further clarification of the role of impaired NO bioactivity and increased MDA level in hypertension could have important implications for the management of hypertension.